Learning Analytics and Student Engagement: Implications for Technology-Based Instruction - Salis Irvan Fuadi; Robingun Suyud El Syam; Dorji Wangchuk (Journal of Paddisengeng Technology, 2025)
Background. Student engagement is a crucial factor that influences academic performance and learning outcomes in technology-based instruction. The increasing integration of learning analytics in educational environments provides valuable insights into how students engage with online learning platforms and tools. However, understanding the relationship between learning analytics and student engagement, and its implications for teaching practices, remains underexplored. Purpose. This study aims to explore the role of learning analytics in enhancing student engagement in technology-based instruction. Specifically, it investigates how data-driven insights can be used to monitor and improve student participation, motivation, and interaction within digital learning environments. Method. A mixed-methods approach was employed, involving a combination of quantitative data from learning analytics platforms and qualitative data from student surveys and interviews. The study was conducted across three universities that integrate technology-based instruction in various disciplines, involving 500 students in total. Statistical analysis was used to identify patterns in student engagement, while thematic analysis was applied to qualitative data to uncover students’ perceptions of technology-enhanced learning. Results. The study found that learning analytics significantly contributes to identifying disengaged students and offering tailored interventions. Moreover, students who received real-time feedback based on analytics showed improved engagement levels, particularly in interactive online modules. The findings also revealed that students valued personalized learning experiences facilitated by data insights but expressed concerns over privacy issues related to data collection. Conclusion. This research highlights the potential of learning analytics to improve student engagement in technology-based instruction. By leveraging data-driven insights, educators can personalize learning experiences and enhance student participation. However, ethical considerations regarding data privacy and the balance between automation and human interaction need to be addressed to ensure a positive impact on learning outcomes.